BAKED POTATO: TREN VIRAL DALAM USAHA CAMILAN DI ERA DIGITAL - Talumikir, Samuel Geraldo; Vidyarto Nugroho (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Baked potato has become a viral phenomenon in the snack industry in the digital age, attracting the attention of various demographics, especially the younger generation. This snack offers delicious flavors and ease of preparation, with a variety of toppings that enhance its appeal. The popularity of baked potatoes has surged alongside the influence of social media, which has transformed how people interact with food and discover new snack options. A notable success story is Ben Newman, known as